2017
DOI: 10.2147/ijn.s147740
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anticancer activity and oral bioavailability of ellagic acid through encapsulation in biodegradable polymeric nanoparticles

Abstract: Despite the fact that various studies have investigated the clinical relevance of ellagic acid (EA) as a naturally existing bioactive substance in cancer therapy, little has been reported regarding the efficient strategy for improving its oral bioavailability. In this study, we report the formulation of EA-loaded nanoparticles (EA-NPs) to find a way to enhance its bioactivity as well as bioavailability after oral administration. Poly(ε-caprolactone) (PCL) was selected as the biodegradable polymer for the formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 45 publications
3
60
0
Order By: Relevance
“…In a study by Mady and Shaker on the preparation of ellagic acid-polymeric nanoparticles using the emulsion-diffusion-evaporation method, the results showed that they were able to sustain the diffusion release of ellagic acid and enhance its cytotoxicity (6.9-fold) against the colon adenocarcinoma, thus improved ellagic acid bioavailability and its anticancer efficacy [32]. Rocha et al also proved the efficacy of using polymeric nanoparticles in delivery of catechin for prostate cancer treatment [33].…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…In a study by Mady and Shaker on the preparation of ellagic acid-polymeric nanoparticles using the emulsion-diffusion-evaporation method, the results showed that they were able to sustain the diffusion release of ellagic acid and enhance its cytotoxicity (6.9-fold) against the colon adenocarcinoma, thus improved ellagic acid bioavailability and its anticancer efficacy [32]. Rocha et al also proved the efficacy of using polymeric nanoparticles in delivery of catechin for prostate cancer treatment [33].…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Found in many fruits (especially pomegranates, raspberries, blueberries, strawberries, walnuts, and grapes) (Hajipour et al., 2018), ellagic acid (EA) is a type of antioxidant that is naturally occurring and widely used for cancer treatment (Verotta et al., 2018). Recent studies have described EA as a naturally occurring bioactive polyphenolic substance (Mady & Shaker, 2017). In addition to its advantages, the disadvantages of EA include poor solubility (9.7 µg/mL) in water at pH 7.4, poor permeability and poor stability at physiological pH for hepatic metabolisms (Madrigal‐Carballo et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…All these studies revealed that these modifications improve the anticancer effects of EA. In another study, Mady et al found that the encapsulation of EA nanoparticles in Poly ε‐caprolactone (PCL) increases the oral bioavailability and activity of EA (Mady & Shaker, ). However, in our knowledge, there is no well‐known method to increase the bioavailability of EA and further investigations seem to be necessary.…”
Section: Resultsmentioning
confidence: 99%